1999
DOI: 10.1128/jb.181.17.5149-5159.1999
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Proteins Involved in Pilus Synthesis and Mating Pair Stabilization from the Related Plasmids F and R100-1: Insights into the Mechanism of Conjugation

Abstract: F and R100-1 are closely related, derepressed, conjugative plasmids from the IncFI and IncFII incompatibility groups, respectively. Heteroduplex mapping and genetic analyses have revealed that the transfer regions are extremely similar between the two plasmids. Plasmid specificity can occur at the level of relaxosome formation, regulation, and surface exclusion between the two transfer systems. There are also differences in pilus serology, pilus-specific phage sensitivity, and requirements for OmpA and lipopol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 85 publications
1
51
0
Order By: Relevance
“…This region has a 6% lower GC content than the genome average and a high percentage of ORFs, which either cannot be assigned to any function or are related to DNA binding and repair, plasmid stabilization or genetic mobilization. The genes related to genetic mobilization include several ORFs presumably encoding proteins similar to the Tra system (Anthony et al, 1999). Some single phage proteins were found in that region and an analysis with the phage finder software PHISPY (Akhter et al, 2012) revealed the presence of a putative prophage spanning the whole 150 kb region.…”
Section: Resultsmentioning
confidence: 99%
“…This region has a 6% lower GC content than the genome average and a high percentage of ORFs, which either cannot be assigned to any function or are related to DNA binding and repair, plasmid stabilization or genetic mobilization. The genes related to genetic mobilization include several ORFs presumably encoding proteins similar to the Tra system (Anthony et al, 1999). Some single phage proteins were found in that region and an analysis with the phage finder software PHISPY (Akhter et al, 2012) revealed the presence of a putative prophage spanning the whole 150 kb region.…”
Section: Resultsmentioning
confidence: 99%
“…All these phenotypes are consistent with a failure of the initiation or elongation of F-pilus filaments. Anthony et al (1999) reported that traB2 and traV569 mutants could still be infected by M13K07, as measured by transduction of kanamycin resistance, albeit at reduced levels. This would suggest a failure of filament elongation, as M13 binds to the tips of F-pili.…”
Section: Discussionmentioning
confidence: 99%
“…Other conjugative elements which contain F-type T4SS include, besides the F factor (E. coli) [7], R100 (IncFII) [32], pED208 (IncFV; S. typhi) [39], R27 (IncHI1; S. typhi) [78], Rts1 (IncT; Proteus vulgaris) [79], R391 (IncJ; Providencia rettgeri) [80], SXT element (Vibrio cholerae) [81] and pNL1 (Novosphingomonas aromaticivorans) [82] (Fig. 1).…”
Section: Relationships Between F-and P-type T4ssmentioning
confidence: 99%
“…Some evidence is available that suggests the T4SS system of F penetrates the recipient cell. TraG F has been implicated in entry exclusion involving protein^protein interactions between TraG F and TraS F , the entry exclusion protein, located in the donor and recipient cells, respectively [32]. This suggests that TraG F is translocated into the recipient cell and interacts with TraS F to block DNA transfer.…”
Section: The Nature Of the Conjugative Porementioning
confidence: 99%